SIMULATION OF A MATRIX CONVERTER FED INDUCTION MOTOR - Mr. A. Raghavendra Prasad , Mr.K.Rajasekhara Reddy (International Journal of Research Science and Management, 2015)
The output voltages of the variable voltage and variable frequency voltage sources employing voltage source inverter is non sinusoidal. The output current of a variable frequency current source using current source inverter is also non sinusoidal .When the induction motor is fed by using these inverters odd harmonics will be present in the input supply,because of these inverters output voltage is non sinusoidal. This harmonics do not contribute the output power of the motor , they produce additional losses in the machine. This harmonic losses reduces the efficiency and cause derating of the motor.These limitations can be overcome by using matrix converter because of its unique feature is pure sinusoidal as output .The matrix converter is superior than inverter drives because of its regeneration ability and four-quadrant operation.Therefore it meets the stringent energy efficiency and power quality.